Social partnership as the factor of professional becoming and adaptation of students at the universities - Posokhina S. A. (Interactive science, 2017)
according to the author, the social partnership is considered as the factor of professional becoming and adaptation of students at the universities from the point of view of three-level model at stages of educational order development, employment and competitiveness of young experts. All this demands creation of the special structure uniting all components of vocational counselling.
Keywords: конкурентоспособность; рынок труда; компетентность; адаптация; личностное развитие; трудоустройство; образовательное учреждение; социальное партнерство; профессионально важные качества; профессиональное становление; работодатель; employment; competence; competitiveness; adaptation; labor market; social partnership; personal development; professional becoming; the employer; educational establishment; professionally important qualities